Students’ Experiences of Cooperative Learning in Developing English Reading Comprehension: Evidence from a Polytechnic Context - Sofyan Sukwara Akfan; Festo Andre Hardinsi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This study investigates the role of cooperative learning in supporting students’ English reading comprehension at Politeknik Negeri Fakfak. Adopting a qualitative descriptive approach, the research involved 35 students from the D3 Mechanical Maintenance and Repair Engineering Study Program during a four-week learning period. Data were gathered through classroom observations, semi-structured interviews, and document analysis, and were subsequently examined using thematic analysis. The findings indicate that cooperative learning enhanced students’ reading comprehension by promoting peer scaffolding, collective interpretation of texts, and collaborative clarification of vocabulary and main ideas. In addition, group-based activities encouraged greater engagement, responsibility, and confidence, as students learned in a supportive environment that helped reduce anxiety during reading tasks. These findings suggest that cooperative learning contributes to both the cognitive and affective dimensions of reading comprehension. The study concludes that structured cooperative learning offers an effective pedagogical strategy for developing interactive and meaningful English reading instruction in vocational higher education.